Faktor-Faktor yang Dominan Terhadap Perilaku Belanja Online Mahasiswa Universitas Warmadewa - Ni Luh Made Intan Krisna G. W; Ita Sylvia Azita Azis; Ni Putu Rediatni Giri (Warmadewa Economic Development Journal (WEDJ), 2023)
The phenomenon of online shopping is a form of change that is presented by internet in terms of innovation in shopping. Internet use is increasing popular in society. From the internet world, we can get to know shopping online or online shopping. This study aims to determine the dominant factors on the online shopping behavior of Warmadewa University students. This study uses primary data with exploratory factor analysis techniques. The results of this study indicate that the first factor is lifestyle, the second factor is product and promotion and the third factor is price. The dominant factor for the online shopping behavior of Warmadewa University students as a whole is outlined as the main factor, namely the Payment System which consists of five statement variables.